Penerapan Metode Sabaq, Sabqi dan Manzil Sebagai Kemampuan Dasar Menghafal Al Quran di Sekolah Swasta Islam Utsman Bin Affan - Arfian, Andi (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2023)
Learning the Koran and teaching it is a principle that must be instilled from an early age. An educator must also know the methods that can be used in the learning process. This research aims to determine the application of the Sabaq, Sabqi and Manzil methods as the ability to memorize the Al-Quran in Utsman Bin Affan Islamic Private Elementary and Middle Schools. This method of community service was evaluated using this research in the form of qualitative research. The data collection tools are in the form of interview guides, observation and documentation to obtain data and analyze how to apply the Sabaq, Sabqi and Manzil methods as the ability to memorize the Al-Qur'an in Utsman Bin Affan Islamic Private Elementary and Middle Schools. From the research results, there is an increase in the ability to read the Al-Qur'an using the Sabaq, Saqi and Manzil methods at the Utsman Bin Affan Islamic Private Middle School, this shows that the majority of Utsman Bin Affan Islamic Private Middle School students enjoy studying the Al-Quran using the Sabaq method , Sabqi and Manzil so that they are able to memorize the Al-Qur'an well and correctly.